A Comparison of Different Patch Geometry Effects on Bandwidth - Dilek UZER; S. Sinan GÜLTEKIN; Rabia TOP; Emrah UĞURLU; Özgür DÜNDAR (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, a new microstrip patch geometry, called Seljuk star, is proposed. The performance of the designed antenna is compared with the performances of square and circular microstrip antennas, which are two other popular patch geometries in literature. The design procedure consists of two phases: First, the patch dimensions of circular and square antennas are taken as the same with Seljuk star dimension. Then the patch surface areas of antennas are fixed to the area of Seljuk star patch and patch dimensions are calculated for the new designs. The effect of different patch types on bandwidth are investigated. Rogers Duroid 6010 ( h = 3.175 mm, ɛ r =10.2) is chosen as the substrate of the antennas which are expected to have a bandwidth center at 5800 MHz. All antenna designs are simulated in HFSS. Each individual antenna is intended to be working at a single frequency, but during the simulations multiple resonance are obtained in many designs. Therefore, the bandwidth and frequency comparisons are done for each resonant frequency among themselves. In comparison to the circular patch geometry with the same surface area, bandwidth is improved 10.57 times, as a result. The deviation between the theoretical calculations and simulations is % 1.38 , which is the smallest deviation among all results. Based on this, it is observed that Seljuk star microstrip patch antenna has a better performance when its dimension or surface area is chosen as same with circular or square antennas. The proposed Seljuk star patch shape is believed to have a high potential to be used in future research.